Thermodynamic modeling and analysis of micro gas turbine as a range extender in electric vehicles with the evaluation of battery pack sizing - Syed Umer Bin Arif (00000170424); Dr Adeel Javed (USPCAS-E, NUST, Islamabad, 2019)
TH-138
Keywords: MS-TEE Thesis MS Thesis